2018
DOI: 10.1111/mve.12304
|View full text |Cite
|
Sign up to set email alerts
|

The status of Demodex cornei: description of the species and developmental stages, and data on demodecid mites in the domestic dog Canis lupus familiaris

Abstract: Demodecosis canina is one of the most important dog parasitoses, but its aetiology is still not well known. There are currently two known species of demodecid mite specific to the domestic dog Canis lupus familiaris Linnaeus, 1758 (Carnivora: Canidae). These are Demodex canis Leydig, 1859 (Acariformes: Demodecidae) and Demodex injai Desch & Hillier, 2003. There have also been many reports of the so-called 'short form', considered to be a separate species functioning under the name Demodex cornei nomen nudum, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
14
0
4
Order By: Relevance
“…The female adult mites were approximately 50% longer and males 100% longer than adult D. canis mites respectively. A short‐bodied mite was named D. cornei by some authors because it was supposedly found more superficially . Genetic comparisons revealed only one or two different species of Demodex in the dog: D. canis and D. injai .…”
Section: Demodex Species In the Dog And Catmentioning
confidence: 99%
See 1 more Smart Citation
“…The female adult mites were approximately 50% longer and males 100% longer than adult D. canis mites respectively. A short‐bodied mite was named D. cornei by some authors because it was supposedly found more superficially . Genetic comparisons revealed only one or two different species of Demodex in the dog: D. canis and D. injai .…”
Section: Demodex Species In the Dog And Catmentioning
confidence: 99%
“…In one report it was suggested that D. cornei are dead or near‐dead D. canis mites, further supporting that only two species of mites exist . However, a taxonomic analysis found the short‐bodied mite to be a distinct canine species …”
Section: Demodex Species In the Dog And Catmentioning
confidence: 99%
“…Demodex injai is substantially larger than D. canis , with adult males and females reported as approximately 100% and 50% larger than D. canis , respectively, 16 and genetically distinct 17 . Demodex cornei is shorter than D. canis , and in a recent study focusing on taxonomic features such as the shape and position of the female opisthosomal organ, the authors concluded that D. cornei could be distinguished from D. canis and D. injai 18 . However, D. cornei was 98% identical to D. canis in a study of the mites mitochondrial 16S rDNA sequence, though D. injai was only 77% identical to D. canis 17 …”
Section: Morphology and Speciesmentioning
confidence: 99%
“…The Demodecidae (Acariformes: Prostigmata) of carnivoran mammals have been relatively poorly studied. Most information regarding mites of the genus Demodex concern domestic animals, dogs and cats, each harboring four species; however, some of these have been discovered only in recent years ( Izdebska and Rolbiecki, 2018 , 2020 ; Morita et al, 2018 ). The majority of known information concerns the clinical signs of the parasitosis in the hosts, canine demodecosis and feline demodecosis , respectively.…”
Section: Introductionmentioning
confidence: 99%